What the empirical studies on sport coach education programs in higher education have to reveal: A review - Trudel, P.; Milestetd, M.; Culver, D. M. (International Sport Coaching Journal, 2020)
Facing the increase in the number of publications, often spread across many journals, researchers have developed different approaches to review the literature. In the first part of this article we present the result of an "overview" type of review of literature on sport coach education programs in higher education (HE) between 2000-2018. By sharing the list of the 38 articles found, along with some general characteristics of these, our hope is, as suggested in many reviews of literature, that researchers will use the review to more easily frame their studies and discuss their results. However, there are very few examples of how this is done. We would argue that how researchers use the same review of literature varies depending of their context, research interests, and research paradigm. Therefore, in the second part of the article we highlight what we took from our review of the literature based on our specific research context—Brazilian HE sport coach education programs. The three key topics presented and discussed are: (a) the importance of considering the student-coaches` biography, (b) how to prepare student-coaches for reflective practice, and (c) the complexity of internships.